Improved utilization of waist‐to‐height ratio in cardiometabolic risk counselling in children: Application of DMAIC strategy. Issue 2 (31st October 2018) - Gupta, Nidhi; Lteif, Aida; Creo, Ana; Iqbal, Anoop Mohamed; Pittock, Siobhan; Tebben, Peter J.; Hansen, Janet; Heyrman, Mary; Spee, Rebecca; Scanlan‐Hanson, Lori; Kumar, Seema
Abstract: Rationale, aims, and objectives: Waist circumference (WC) and waist‐to‐height ratio (WHtR) are superior surrogate markers of central obesity than body mass index. However, WC is not measured routinely in paediatric clinics. The objective of this study was to implement measurement of WC during routine assessment of children in an ambulatory outpatient clinic setting and subsequent dissemination of cardiometabolic risk counselling in children with central obesity (defined as WHtR ≥0.5). Method: Prospective cohort of patients aged 6 to 20 years. Study period was divided into three phases: baseline (3 months), process improvement (2 months), and implementation (6 months). Define‐Measure‐Analyse‐Improve‐Control (DMAIC) strategy was applied. Measurement of WC was implemented as a component of the physical examination in patients. Outcome measures were (1) improvement in frequency of WC measurement and (2) utilization of WHtR in cardiometabolic risk counselling. Results: Waist circumference was not measured in any patient during baseline phase ( n = 551). During process improvement phase, of the total 347 patients, WC was measured in 35% vs target of 30%. In the implementation phase, WC was measured in 37% patients (365 out of 964). Of these 365 patients, 175 (48%) had elevated WHtR, and 73% of them ( n = 128) were counselled about their increased cardiometabolic risk. Conclusions: Application of an evidence‐based DMAIC protocol led to significant improvement in assessment for central obesity in an ambulatory clinic practice and appropriate counselling regarding cardiometabolic risk reduction in children and adolescents with central obesity over an 8‐month period. Meticulous planning and execution, frequent reinforcement, and integrating feedback from the involved multi‐disciplinary team were important factors in successful implementation of this quality improvement project.